A monovalent cation acts as structural and catalytic cofactor in translational GTPases. (15th September 2014) - Kuhle, Bernhard; Ficner, Ralf
Abstract Translational GTPases are universally conserved GTP hydrolyzing enzymes, critical for fidelity and speed of ribosomal protein biosynthesis. Despite their central roles, the mechanisms of GTP‐dependent conformational switching and GTP hydrolysis that govern the function of trGTPases remain poorly understood. Here, we provide biochemical and high‐resolution structural evidence that eIF5B and aEF1A/EF‐Tu bound to GTP or GTPγS coordinate a monovalent cation (M+) in their active site. Our data reveal that M+ ions form constitutive components of the catalytic machinery in trGTPases acting as structural cofactor to stabilize the GTP‐bound "on" state. Additionally, the M+ ion provides a positive charge into the active site analogous to the arginine‐finger in the Ras‐RasGAP system indicating a similar role as catalytic element that stabilizes the transition state of the hydrolysis reaction. In sequence and structure, the coordination shell for the M+ ion is, with exception of eIF2γ, highly conserved among trGTPases from bacteria to human. We therefore propose a universal mechanism of M+‐dependent conformational switching and GTP hydrolysis among trGTPases with important consequences for the interpretation of available biochemical and structural data.